Fuzzy AHP method to determine headache types based on symptoms [Fuzzy AHP Mtodo para determinar los tipos de cefalea segn los sntomas] - Maseleno A.; Tang A.Y.C.; Mahmoud M.A.; Othman M.; Saputra S.; Muslihudin M. (Instituto de Investigaciones Clinicas, 2023)
analytical hierarchy process; Article; decision making; decision support system; fuzzy multi attribute decision making; fuzzy system; headache; health care personnel; human; information processing; pain; problem solving